Sambut Tahun Baru Belajar Investasi Seru Bersama Siswa/i SMKN Negeri 3 Bengkulu Tengah - Fitriano, Yun; Ariska, Yesi Indian; Tambunan, Dennis Rydarto; Yulianti, Oni; Harwini, Dewi (Jurnal Dehasen Mengabdi, 2024)
Technological changes and developments must be utilized by all groups, not only for consumption but can be used as a tool for investment, investment in this case is stock and capital market investment which can be done by all groups, including students. The problem that occurs at SMKN 3 Central Bengkulu is that students and teachers do not yet fully understand investment in the capital and stock markets. With this problem, the community service team consisting of lecturers from the Faculty of Economics and Business, Dehasen University, Bengkulu, in collaboration with the Indonesian Stock Exchange, representatives of Bengkulu, provided material regarding the capital and stock markets. The solution that the community service team can provide at SMKN 3 Central Bengkulu is to provide assistance in operating the applicationProfits Anywhere which has been downloaded by students and teachers on their respective smartphones. In this case, the method used is preparation, observation and presentation of the FGD. With this activity, students and teachers understand more about capital and stock market transactions and the importance of cultivating an entrepreneurial spirit in life and will later be able to gain profits without just relying on job vacancies from the government and private sectors.